Design And Development Of Underwater Robot For Cleaning Process - Mohd Shahrieel, Mohd Aras; Mohd Khairi, Mohd Zambri; Fadilah, Abdul Azis; Shahrum Shah, Abdullah; Anuar, Mohamed Kassim (Universiti Teknikal Malaysia Melaka, 2016)
This paper shows the conception and growth of an underwater robot for cleaning operation that can help human beings to perform cleaning tasks underwater. Unmanned underwater vehicles can cut down the danger to human life in term of underwater cleaning job where a human can dive and descent at a certain depth and is not able to stay there in a longer period of time. Underwater Robot for cleaning process was a combination between underwater robot such as Remotely Operated Vehicles (ROV) and cleaning part called Underwater Cleaning Robot (UCR). The main objective of this project was to develop a cleaning tool attached to the ROV to demonstrate the performance of the cleaning procedure as in water treatment operations. By the invention of this UCR, more underwater cleaning job can be done without involving human life. This project began with a design using Solidworks software to capture the dynamics of a newly fabricated UCR. The UCR can perform the cleaning task and this project can give much benefit to the related underwater business especially for the cleaning process.